2010
DOI: 10.1007/s10653-010-9343-5
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of lithium in the environment of the Jordan Valley and its transfer into the food chain

Abstract: Lithium is found in trace amounts in all soils. It is also found in plants and in nearly all the organs of the human body. Low Li intake can cause behavioral defects. Thus, this study was conducted to investigate the concentration and distribution of water-soluble Li in soils of the Jordan Valley and its concentration in citrus trees and some important food crops in view of the significant implications of Li for human health. The concentration of soluble Li was measured in 180 soil samples collected at two dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Lithium pollution is a new environmental problem that appeared after the 1990s. This study, together with previous researches, confirms that a high concentration of lithium could cause serious injury to the environment and humans, which needs to be paid more attention to [17,44,45]. However, at present, the indicators of environmental monitoring, such as the detection of soil and water, do not include lithium in the Yangtze River Basin.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Lithium pollution is a new environmental problem that appeared after the 1990s. This study, together with previous researches, confirms that a high concentration of lithium could cause serious injury to the environment and humans, which needs to be paid more attention to [17,44,45]. However, at present, the indicators of environmental monitoring, such as the detection of soil and water, do not include lithium in the Yangtze River Basin.…”
Section: Discussionsupporting
confidence: 61%
“…It needs to add lithium as an indicator as soon as possible, especially in the vulnerable areas. Besides, adding the detection of lithium in agricultural irrigation water is particularly important because it is not only closely associated with the crops, but also with our health [44]. Lithium has been listed as a pollutant that leads to environmental harm in irrigation water supplies in Australia [10].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Li in plants is highly variable [65]. The amount of Li in plants is a function of the amount of Li in the soil substrate in which the plants are growing because of this it has been suggested that the concentration of Li in plants is a good guide to the amount present in the soil [66]. One study reports that Li occurs in plants at levels of 0.15 to 0.3 mg/kg [67].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies showing that at low Li levels, plant growth stimulation has been observed [29,63,64,67,69,[72][73][74][75][76][77]. Species of plants tolerant to Li are found mainly in the Solanaceae and Asteraceae families and are also said to include the Ranunculacae and Rosaceae families [66,68,71,78]. In 2013 a new Li accumulator plant was discovered in China Apocynum venetum.…”
Section: Introductionmentioning
confidence: 99%
“…A range between 10 and 40 mg/kg is generally accepted as the "background" concentration of lithium in soil with average values of 20 mg/kg in the soil and 30 mg/kg in granites (Table S5 [ 14,20,32,45,60,63,66,[70][71][72][73][74][75] and Table S6, Supplementary Material [32,34,39,45,60,[76][77][78][79][80][81][82][83][84][85]). According to some authors, the lithium content of soils is determined more by the conditions of soil formation rather than by its initial content in parent rocks [70,86]. Lithium has been reported to correlate strongly with aluminium in the clay fraction of soils [79].…”
Section: Lithium In Soilmentioning
confidence: 99%